2004
DOI: 10.1111/j.1469-7610.2004.00321.x
|View full text |Cite
|
Sign up to set email alerts
|

Face‐sensitive cortical processing in early infancy

Abstract: We conclude that there is some degree of specificity of cortical processing of faces as early as 3 months of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
143
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 144 publications
(158 citation statements)
references
References 39 publications
(62 reference statements)
12
143
0
3
Order By: Relevance
“…As we have discussed earlier in this chapter, research on face processing and brain activity in typical individuals has concluded that there is a specific area in the brain that is activated when individuals are presented with face stimuli (Farah, 1996;Elgar & Campbell, 2001;Halit et al, 2004). It is well established that when hemispheric asymmetry for face processing is observed, the right rather than the left hemisphere is implicated in face processing, and specifically the middle part of the right fusiform gyrus shows activation and has been named 'Fusiform Face Area' (FFA) (Elgar & Campbell, 2001) (See Chapter 2 for details).…”
Section: Neuropsychological Studies Of Face Processing In Asdmentioning
confidence: 92%
See 4 more Smart Citations
“…As we have discussed earlier in this chapter, research on face processing and brain activity in typical individuals has concluded that there is a specific area in the brain that is activated when individuals are presented with face stimuli (Farah, 1996;Elgar & Campbell, 2001;Halit et al, 2004). It is well established that when hemispheric asymmetry for face processing is observed, the right rather than the left hemisphere is implicated in face processing, and specifically the middle part of the right fusiform gyrus shows activation and has been named 'Fusiform Face Area' (FFA) (Elgar & Campbell, 2001) (See Chapter 2 for details).…”
Section: Neuropsychological Studies Of Face Processing In Asdmentioning
confidence: 92%
“…In a similar line of research, more recently Halit et al (2004) argued that, while evidence from behavioural studies has been useful in testing hypotheses about the typical and atypical development of face processing, issues related to neural specialisation can most directly be addressed through functional neuroimaging. In other words, only by studying and recording event-related potentials (ERPs) someone is able to determine the specificity or otherwise of cortical processing of faces.…”
Section: Face Processing and Brain Activitymentioning
confidence: 99%
See 3 more Smart Citations